Legal Study of Bureaucratic Reform in Improving the Quality of Public Services at the National Narcotics Agency of the Republic of Indonesia (BNN RI) - Dewi Pertasari; Farliandi Farliandi; Lina Yuliana; Suparno Suparno; Sufiarina Sufiarina (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2023)
The illicit trafficking of drugs is a crime that is very broad and transcends the boundaries of a country, can move to all socio-economic layers of society in the world. Drug trafficking is a form of globalization of organized crime. The approach method used in this research is normative juridical legal research, namely legal research conducted by researching and studying literature. According to Soedjono Soekanto and Srie Mamuji, normative legal research includes: research on legal principles, legal systematics, levels of vertical and horizontal synchronization, comparative law and legal history. BNN RI, needs to represent institutional performance that must be oriented towards performance results that can be felt by the community. This professional and high-performing institutional strengthening will provide transformation points that have an impact on improving public services. The indicator of the success of this goal is measured by the Public Service Index. For the obstacles faced in Bureaucratic Reform in improving public services at the National Narcotics Agency of the Republic of Indonesia (BNN RI), that there are several factors that influence the not running of public services properly at the National Narcotics Agency of the Republic of Indonesia (BNN RI), namely employee performance problems that is not good, such as behavior that does not reflect serving optimally shows behavior that wants to be served